1986
DOI: 10.1111/j.1439-0264.1986.tb00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of Spermatogenesis and Sertoli Cells (Epitheliocytus sustentans) in the Bull

Abstract: The fine structure of spermatogenesis and Sertoli cells in bulls has been described. New observations and data from the literature have been compiled to give a comprehensive description of the complicated differentiation processes and cellular relations in the seminiferous epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
5

Year Published

1987
1987
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 30 publications
0
16
0
5
Order By: Relevance
“…The ultrastructural features of buffalo primary spermatocytes generally resemble those of the bull (EKSTEDT et al, 1986), but some conspicous differences were observed.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The ultrastructural features of buffalo primary spermatocytes generally resemble those of the bull (EKSTEDT et al, 1986), but some conspicous differences were observed.…”
Section: Discussionmentioning
confidence: 82%
“…The second way to divide the seminiferous epithelial cycle uses cellular associations of defined composition in conjunction with variations in shape and localization of spermatids. This method has been established for a number of domestic animals (CLERMONT, 1972;FOOTE et al, 1972;SWIERSTRA et al, 1974;EKSTEDT et al, 1986), leads to a restricted number of stages (mostly 8), and is especially well suited for comparative and quantitative studies. According to this latter method the spermatogenic cycle in the buffalo seminiferous epithelium is divided into 8 stages with accomplished spermiation as the demarcation between the two cycles, as has been proposed by EKSTEDT et al (1986) for the bovine seminiferous epithelium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of studies in many mammals have been made on their morphological characteristics using light and transmission electron microscopy (ELFTMAN, 1950(ELFTMAN, , 1963NISHIDA, 1954;FAWCETT and BURGOS, 1956;DYM, 1973;FAWCETT, 1975;KAYA and HARRISON, 1976;OSMAN andPLOEN, 1978, 1986;PLOEN and RITZEN, 1984;EKSTEDT et al, 1986), the three-dimensional configuration was never accurately described, probably because of its complicated morphological features as well as its close attachment to germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few reports detailing spermiogenesis in birds are to be found in the literature. 1,4,5,6,8,9,14,15, Most of these publications are, understandably, on the more economic domestic species of birds, such as the domestic fowl, turkey, duck and quail, [21][22][23][24][25]27,29,30,42,[47][48][49][50][51] and even much fewer on other species of birds, including passerines and the Paleognathae. 22,33,35,37,41,42,[44][45][46]49,52 However, most of these publications are based upon individual or fragmentary organelle development 30,[37][38][39][40]45,46 rather than the non-fragmentary method of spatiotemporal, in-tandem, development of the early spermatid in the Japanese quail, 49 in the Turkey, 42 in the House Sparrow, 41 in the parrot, 45 in the Ostrich, 37 in the European nightjar (Caprimulgus europaeus) …”
Section: An Overview Of Spermiogenesis In Birdsmentioning
confidence: 99%